The effect of financial constraints on in-group bias: Evidence from rice farmers in Thailand - Boonmanunt S. (2023)
In-group bias can be detrimental for communities and economic development. We study the causal effect of financial constraints on in-group bias in prosocial behaviors – cooperation, norm enforcement, and sharing – among low-income rice farmers in rural Thailand, who cultivate and harvest rice once a year. We use a between-subjects design – randomly assigning participants to experiments either before harvest (more financially constrained) or after harvest. Farmers interacted with a partner either from their own village (in-group) or from another village (out-group). We find that in-group bias in cooperation and norm enforcement is not increased by financial constraints. By contrast, the results seem to suggest that in-group bias exists only after harvest, that is, when people are less financially constrained.